Genistein Reduces Anxiety-like Behavior During Metestrus–Diestrus Phase Without Changing Estradiol or Progesterone Levels in Wistar Rats - Juan Francisco Rodríguez-Landa; Oscar Jerónimo Olmos-Vázquez; Carlos Fabrizio Quiñonez-Bailón; Gabriel Guillén-Ruiz; Ana Karen Limón-Vázquez; Jonathan Cueto-Escobedo; Eduardo Rivadeneyra-Domínguez; Blandina Bernal-Morales (Metabolites)
Background: Premenstrual syndrome is characterized by emotional changes, including anxiety and depression symptoms, which may be treated with anxiolytic and antidepressant drugs, as well as estrogen therapy. However, steroidal estrogen therapy is contraindicated for patients with a potential risk of developing estrogen-dependent cancers through interactions with estrogen receptor α (ERα). Alternatively, genistein produces estrogenic effects in animals and humans at dietary dosages that act on the nuclear and membrane ERα, estrogen receptor β (ERβ), and the G-protein-coupled estrogen receptor (GPER). These receptors are likely involved in the anxiety symptoms observed in premenstrual disorders. The objective of this study was to evaluate the effects of genistein and 17β-estradiol on anxiety-like behavior and the plasma concentrations of estradiol and progesterone throughout the ovarian cycle of Wistar rats. Methods: The effect of the administration of 0.09 mg/kg of genistein or 17β-estradiol was evaluated using the elevated plus maze (EPM) test, locomotor activity test (LAT), and light/dark box (LDB) test, as well as by assessing the plasma concentrations of estradiol and progesterone, while considering the ovarian cycle phases. Results: Higher levels of anxiety-like behavior were detected in the metestrus–diestrus phase compared to the proestrus–estrus phase, which was associated with low concentrations of estradiol. Genistein, similarly to 17β-estradiol, significantly reduced anxiety-like behaviors in the EPM and LDB; however, 17β-estradiol, but not genistein, significantly increased the plasma estradiol concentration. No significant changes were found in locomotor activity or the plasma progesterone concentrations due to the treatments. Conclusions: These findings suggest that genistein may be useful in the development of alternative therapies to reduce the anxiety associated with low steroid hormone concentrations, which occur in premenstrual syndrome. Genistein could be an alternative to steroidal estrogen therapy to avoid potential side effects due to estradiol or antidepressant treatments, although it still requires medical care.